Improvement of the land reclamation systems in irrigable agriculture of Ukraine in the ХХ century - Kovalenko, N. P. (History of science and technology, 2016)
Basic directions of development of theoretical and practical bases of development and introduction of the land reclamation systems are set in irrigable agriculture of Ukraine in the ХХ-th century. The process of improvement of technical providing of the land reclamation systems is represented from the superficial watering to artificial overhead irrigation and tiny irrigation. Their efficiency is justified from the economic, power and ecological points of view.